Principios distributivos y pensiones no contributivas en Argentina, Bolivia y México - Sandoval Álvarez, Benjamín (El Colegio de México, 2019)
In recent years, several Latin American countries have implemented different strategies to extend old-age pension coverage to older adults previously excluded from traditional social security. While they share the adoption of not-strictly contributory mechanisms, these strategies vary in the distributive principles and the models of solidarity and equity underlying them, so they have different distributive impacts. In particular, this paper analyzes three strategies: Argentina illustrates a model guided to some extent by the contributory principle, Bolivia is inclined to a model based on the principle of citizenship, and Mexico illustrates a model guided by the principle of necessity. The relevance of this article is to discuss the principles that characterizes different pension schemes in Latin America.